2019
DOI: 10.3390/educsci9020074
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Both Individual and Collaborative Job Crafting on Spanish Teachers’ Well-Being

Abstract: Current changes in social structures and political-economic systems directly affect teachers’ job performance. Among others, these changes include changes in communication and information technologies, the scientific revolution, changes in the structure of populations, the revolution of social relations, economic and political transformations, and revolutions in labor relations and leisure time. These changes all seem to have promoted educational revolutions, which encourage the development of autonomous indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 47 publications
1
23
0
3
Order By: Relevance
“…Early conceptualisations of the JD-R theory assumed that employees had little control over working conditions, which were considered to be established by employers and organisations (Bakker and Demerouti 2017). However, longitudinal tests of JD-R theory have found that employees often make proactive changes to optimise their workplace experiences (e.g., by actively seeking challenges, mobilising job resources, and finding ways to manage their job demands; Alonso et al 2019;Tims et al 2013). This process, referred to as job crafting, is an example of the way in which JD-R theory can be practically applied to enhance teacher wellbeing.…”
Section: Implications-bridging the Gap Between Research And Practicementioning
confidence: 99%
“…Early conceptualisations of the JD-R theory assumed that employees had little control over working conditions, which were considered to be established by employers and organisations (Bakker and Demerouti 2017). However, longitudinal tests of JD-R theory have found that employees often make proactive changes to optimise their workplace experiences (e.g., by actively seeking challenges, mobilising job resources, and finding ways to manage their job demands; Alonso et al 2019;Tims et al 2013). This process, referred to as job crafting, is an example of the way in which JD-R theory can be practically applied to enhance teacher wellbeing.…”
Section: Implications-bridging the Gap Between Research And Practicementioning
confidence: 99%
“…Job satisfaction can be improved by job crafting as people can redefine their job to meet their needs and increase the applicability, meaning, and purpose of their work [ 11 , 19 ]. Recently, some scholars have indicated that individual and collaborative job crafting positively influences the job satisfaction of hotel employees and teachers [ 29 , 32 , 33 ]. The author indicated that job crafting has a significant positive impact on job and life satisfaction [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other, many difficulties may arise, such as lack of time, lack of confidence, or lack of training (Donaldson and Mavrogordato, 2018). Since well-being is conceptualized as a self-realization, as a social integration and as positive orientation toward the task, job satisfaction, life satisfaction and job performance are often used as its indicators (Alonso et al, 2019). Teachers’ performance appraisal aims to be an objective system evaluating teachers and teaching through a supervisors’ analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Work context and life domain are not distinct spheres: they are interdependent and could influence each other in many ways (Chummar et al, 2019). Then, we would like to take a further step: to explore the relation between performance appraisal justice and life satisfaction, which is often used as an indicator of well-being (Alonso et al, 2019). Life satisfaction is a cognitive evaluation regarding how satisfying our entire life is (Hart, 1999).…”
Section: Introductionmentioning
confidence: 99%